Novel preparation and characterization of porous alginate films - Wang, X; Li, X; Stride, E; Huang, J; Edirisinghe, M; Schroeder, C; Best, S; Cameron, R; Waller, D; Donald, A (2010)
Porous alginate films were prepared using a novel route in which alginate solutions of similar surface tensions but different viscosities were bubbled using a T-junction device to generate the films. The relationship between bubble size and bubbling conditions such as solution flow rate and air pressure was systematically investigated. The films obtained were characterized by optical microscopy, combined focused ion beam/scanning electron microscopy, and ultrasound reflection measurements. It is concluded that in a film, the thickness can be varied from 1-40 μm, where the minimum and maximum represent bubble-free and bubble-containing areas, respectively. Based on the characterization results obtained, a possible structure for the bubbles in the films is hypothesized. © 2010 Elsevier Ltd. All rights reserved.